Effect of Nanoparticles and Ionization Radiation on Same Oxidant and Antioxidant Enzymes - Rafal Dawood Ali; Baydaa T. Sih; Dakhel Ghani Omran (Institute of Medico-legal Publications Pvt Ltd, 2021)
Ionizing radiation effect on atoms and molecules of living organisms by formation of free radicalsbecause it has high energy radiation which causes gain or loss one electron or more. In last year’sthere are a biggest interest for using nanoparticles in medicine as a drag delivers or cancer treatments, as its will knew. The present research was focused to evaluate the effects of X- ray and nanoparticles(alone or together) on level of Malondiahyed ( MDA ) , it is the final product of oxidative reactions ,and, on the other hand , alleviate these effects by addition of vitamin – E ( as anti- oxidant ) in bloodsamples in-vitro. Results which were yield from this research indicated that level of MDA had beensignificantly increased when blood samples exposed to X- rays but its values were significantly droppedin the presence of nanoparticles of titanium dioxide (TiO2) in a comparison with those non- treatedblood samples ( control samples ) . It was well found that levels of MDA were markedly decrease inthe samples treated with V- E after exposure them with both X-ray and nanoparticles . From thoseobservations , it appear that exposure of living tissues to X-rays and nanoparticles causing productionof free radicles ( oxidative stress ) and these adverse effects can be limited and ameliorated by treatmentwith antioxidant vitamins .